Meta-analysis of prognostic factors in patients with knee arthroplasty - Guo, Fengying; Shi, Xiaoxia; Song, Honghui; Wang, Shendong (Frontiers in Surgery, 2025)
ObjectiveTo identify specific factors predicting functional outcomes, pain reduction, and patient satisfaction following knee arthroplasty through systematic review and meta-analysis.MethodsA comprehensive search of multiple databases (Pubmed, Embase, OVID, Medline, Cochrane Library, CNKI, Wanfang, VIP) was conducted for studies published from database inception to December 2024. Studies reporting associations between preoperative factors and standardized outcomes after knee arthroplasty were included. Two reviewers independently screened articles, extracted data, and assessed study quality using modified Jadad scale for randomized trials and MINORS for non-randomized studies. Random-effects meta-analyses were performed for pain duration and red blood cell distribution width (RDW), with meta-regression to assess their prognostic value for functional outcomes measured by standardized knee scores. Heterogeneity was assessed using I2 statistics, and publication bias was evaluated using Egger's and Begg's tests.ResultsEight studies were included in the final analysis: Four studies examining pain duration (n = 576 patients) and four studies examining RDW (n = 612 patients) met inclusion criteria. Significant heterogeneity was observed in both analyses (I2 = 87% and I2 = 91%, respectively, p < 0.01). Meta-regression revealed that shorter pain duration (<3 years) was significantly associated with better functional outcomes at 12-month follow-up [Weighted Mean Difference (WMD) = −4.532, 95%CI = (−6.439,−2.626), p < 0.001]. Normal preoperative RDW values (11.5–14.5%) were also significantly associated with improved functional outcomes [WMD = −1.742, 95%CI = (−2.371,−1.114), p < 0.001]. Subgroup analyses indicated that the predictive value of these factors was consistent across different surgical techniques (p = 0.42). Publication bias assessment showed no significant bias (Egger's test p = 0.2094, Begg's test p = 0.0833). The high heterogeneity limits the direct clinical application of these pooled estimates and necessitates cautious interpretation.ConclusionThis meta-analysis identified shorter preoperative pain duration and normal RDW values as independent predictors of better functional outcomes following knee arthroplasty. However, the small number of included studies and high heterogeneity observed warrant cautious interpretation of these findings. These findings can help clinicians identify patients at risk of suboptimal outcomes and potentially guide personalized perioperative interventions. Further research is needed to establish optimal cutoff values and to evaluate the combined predictive power of these factors in clinical practice.